Requirement Modeling for Academic Data Inventory System in Faculty of Computer Science Sriwijaya University - Rahmat Izwan Heroza (Annual Research Seminar (ARS), 2015)
Faculty of Computer Science, Sriwijaya University, manages a lot of data used in the process. Academic is one of the field that contain important data such as curriculum, lecturer, academic mentor, final projects and other process related to academic. Besides of big number, academic data also used in departments other than academic department. It is difficult to distribute while maintaining academic data without a computerized system. This paper attemps to propose a requirement model for academic inventory system that can be used as a model so academic data can be distributed easily while maintained. Faculty of Computer Science, Sriwijaya University, used as a case study of the problem.